Penambahan Bekatul dan Angkak pada Produk Agar-agar sebagai Alternatif Cemilan Pengikat Kolesterol - Hasim Hasim; Didah Nur Faridah; Ditha Mithania (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2019)
The prevalence of hypercholesterolemia in Indonesia reaches 11.2%. Hypercholesterolemia can occur due to lack of exercise, consume too much food containing fat and cholesterol, and lack of fiber intake. Rice bran and red yeast rice contain fiber and phytochemical compounds that can reduce cholesterol, including alkaloids, saponins, tannins, flavonoids, and phenolics. The purpose of this study is to use rice bran and red yeast rice as an alternative snack that can potentially bind cholesterol. Rice bran and red yeast rice are added to agar to obtain gelatin snacks with high fiber content and phytochemical compounds. Agar is made into three formulas. Hedonic rating tests have been carried out, so that obtain the formula that is most preferred by consumers. The test results show that the formula with the addition of sodium citrate of 0.3% is most preferred, with the addition of bran and red yeast rice each of 30 and 0.8 grams and the use of agar for 7 grams. Gelatin products contain 14.80% food fiber and total flavonoids by 0.02%. The total phenolic was not detected in agar products. The results of the cholesterol-binding test in vitro showed that gelatin products can bind cholesterol by 60.11%.